HUBUNGAN MOTIVASI DENGAN LAMANYA MASA TUNGGU KERJA PADA LULUSAN FAKULTAS KEPERAWATAN UNIVERSITAS SUMATERA UTARA PERIODE 2008 DAN 2009 - Fitri, Ainil (PROGRAM STUDI DIII KEPERAWATAN UNIVERSITAS ABDURRAB PEKANBARU, 2016)
Work motivation is defined as the strength, encouragement, needs, pressure, or psychological mechanism that encourages a person to achieve the feat in work or employment. The length of the waiting period of work is the time needed to obtain a first job after graduation. This study aims to determine the relationship between motivation and the length of the waiting period of work. The study population was all graduates of the Faculty of Nursing USU regular period of 2008 and 2009, which amounted to 57 people. While the study sample was taken by purposive sampling technique that is equal to 49 people. The method used is the method correlation study. Data collection instruments are arranged in the form of a questionnaire developed by researcher using Likert scale. Data were analyzed using Spearman correlation test and regression. Based on the results obtained Spearman correlation of 0.366 strength. This means that there is a relationship between motivation and the length of the waiting period of work. To obtain regression test motivating force that most contributed to increasing the motivation is the power demoktratik and technocrats as to the type of motivation that many contribute is external motivation. The conclusion is that there is a positive relationship between motivation and the length of the waiting period of work. Suggestions for further research is to identify factors that affect the length of the waiting period of work and looking for which factors most affect the length of the waiting period on graduate work in addition to motivation. For the future of nursing education are expected to be able to facilitate students in obtaining a job as an announcement of jobs, training to facilitate employability and anything else that makes it possible to shorten the length of the waiting period on graduate employment.